Effect of Acrylic Polymers on the Physical Parameters and in vitro Release Kinetics of Diclofenac Sodium Sustained Release Pellets (Bangladesh Journal of Scientific and Industrial Research, 2008)
The aim of the present study is to investigate the effect of Ammonio Methacrylate Copolymer Type A (Eudragit RL 30 D) and Ammonio Methacrylate Copolymer Type B (Eudragit RS 30 D) on the release kinetics study of diclofenac sodium form coated pellets. Eudragit RS 30 D and Eudragit RL 30 D were added into the formulation at 5:1 ratio. Different percent of this polymeric combination was loaded on to the drug-loaded pellets. Loss on drying value as well as bulk density of coated pellets increase along with the increase in polymer level. It was found that the cumulative percent release of drug decreased with the increase of polymer load in all cases. From all formulations it was observed that the release of diclofenac sodium in 0.1N HCl media was very low (maximum 2.87 %) at first 2 hours. Better sustaining effect was found from Eudragit RS 30 D and Eudragit RL 30 D combinations. Drug was released linearly along with time throughout the whole dissolution process in phosphate buffer (pH 6.8) and it was also revealed that, in all cases the release of diclofenac sodium followed zero order kinetics. Key words: Diclofenac sodium, Eudragit RL 30 D, Eudragit RS 30 D, Aqueous coating, Physical parameters, Kinetics of drug release Bangladesh J. Sci. Ind. Res. 42(3), 239-248, 2007